Assesing compressive strength variations of galam wood in construction: A study of different sections and ratios - Asnan, Muhammad Noor; Khoirulliyah, Ayu Arina; Noor, Rusandi; Vebrian, Vebrian (Jurnal Teknika, 2023)
Due to of its inherent strength and durability, wood is a valuable and abundant natural resource that is frequently used in the construction industry, road infrastructure, and bridge architecture. Notably, Galam Wood stands out as a distinct possibility for construction applications, as it may be used in its natural state without the need for specialist treatments. The current research digs into an examination of several areas of Galam Wood, including the bottom, middle, and higher regions. This inquiry integrates distinct ratios (1, 2, 3, 4, and 5) to investigate their respective influences on the material's strength. The chosen diameter of the specimens, varying between 5 cm and 10 cm, emerges as a critical element impacting compressive strength. In the size conditions of 10 cm diameter specimens, differences in section reveal a minimal influence on compressive strength, contrasting significantly with the considerable effect reported in the 5 cm diameter test items. The observable dissimilarity in compressive strength readings for the 10 cm diameter specimens remains below the threshold of 10%. Nevertheless, the careful selection of diverse ratios distinctly modifies the compressive strength outputs, underlining the critical function of this parameter in the behavior of Galam Wood under compressive loads.